School Environment from Physical Aspects to Learning - KAUL, ANJNI (THE PRIMARY TEACHER, 2015)
School is a place where teachers and students interact both formally and informally. In this paper author has tried to examine the physical environment of a school such as teacher-pupil ratio, school building, activity room, library, classroom space, outdoor space, furniture, staff provided, along with aspects such as gender issues, inclusive education, space for parents and community etc. Author has also tried to find out if school and classroom environment is reasonably good, to what extent it would really be responsible for influencing students learning. Even though environment of the school is satisfying but educational practice is still based on limited lesson plans as indicated in the present study. Tasks are repetitive, mechanical and focus is on outcomes only